Effect of Light on Growth and Uptake of Nutrients on some Forest Tree Seedlings - Bhatnagar, H. P. (Indian Forester, 1966)
Pot culture experiment was conducted to determine the effect of different light conditions on the growth and uptake of nutrients on forest tree seedlings. The species investigated were teak, chir, hollong and Casuarina equisetifolia. The results of the experiments have indicated that teak, chir and Casuarina equisetifolia prefer relatively good light conditions (approximately 94% of the day light). Hollong on the other hand prefers relatively medium light condition (approximately 22% of the day light). The dry weights of all the species are directly correlated with the height growth. As regards the effect on the uptake of minerals it may be mentioned that uptake of nitrogen has not shown any regular trend except in the case of Casuarina equisetifolia, where it is inversely corelated with the availability of light. Uptake of potassium and phosphorus on the other hand have shown regular trend in all the species. In respect of chir, teak and Casuarina these elements are inversely correlated with the availability of light.